Analysis of Indigenous Papuan Students’ Preferences for Learning Methods in Higher Education - Meylani Aljeinie Tijow; Febi Adriana Mutiara Sogalrey (Institut of Shanti Bhuana, 2026)
This study aims to identify dominant learning method preference patterns among indigenous Papuan students and formulate adaptive learning strategy recommendations. The research employed a quantitative descriptive method with survey techniques involving 124 indigenous Papuan students at Cenderawasih University, consisting of 90 Social Humanities (Soshum) and 34 Science and Technology (Saintek) students. Data were collected using structured questionnaires with 5-point Likert scale measuring preferences for ten learning methods. Results showed that Experiential Learning had the highest preference (Soshum 95.6%, Saintek 96.9%), followed by Lecture Method (Soshum 92.2%, Saintek 97.0%) and Small Group Discussion (Soshum 94.4%, Saintek 91.2%). Online Learning received the lowest preference (Soshum 44.4%, Saintek 31.2%). Significant differences existed between groups, with Soshum students preferring social interaction-based methods while Saintek preferred structured methods. Furthermore, another interesting finding is that a significant number of both Soshum and Saintek students surprisingly still prefer the lecture method. These findings provide empirical basis for designing more adaptive and inclusive learning strategies for indigenous Papuan students. Overall, the results of this study provide an empirical basis for designing learning strategies that are more adaptive and inclusive for indigenous Papuan students, with the hope of increasing learning motivation and reducing disparities in academic achievement among students 3T (frontier, outermost, and underdeveloped) backgrounds.